The Effect of Polychronicity on Turnover Intention with Mediation of Job Satisfaction and Employee Engagement and Moderated by Work Environment - Rahmadhanti; Muhammad Donal Mon; Adi Neka Fatyandri (Jurnal Manajemen, 2025)
This study investigated the knowledge the relationship between job satisfaction, polychronicity, employee engagement and job satisfaction moderated by work environment. The quantitative study used a survey method to collect data with purposive sampling and technique. The survey was conducted on 360 employees from various manufacturing companies in Batam City. The data was analyzed using the structural equation modeling partial least square technique processed with smart-pls. The study’s findings were as follows: polychronicity positive and significantly affected employee engagement, job satisfaction and turnover intention. Job satisfaction also positive and significantly affected employee engagement. Work environment also positive and significantly affected job satisfaction. Job satisfaction negative and significant affected turnover intention. Employee engagement negative and not significant affect Turnover intention. In the meantime, work environment moderated job satisfactions and polychronicity.